To recommend or to regret the choice? Factors explaining student loyalty: evidence from the catalan university system - Berbegal-Mirabent, Jasmina (2020)
This study analyses the determinants of students’ loyalty and seeks to characterise the profile of recent university graduates. The empirical application considers the region of Catalonia, in Spain. Data come from the Satisfaction Graduate Survey elaborated by the Catalan University Quality Assurance Agency. A total of 2,557 questionnaires were collected. Results reveal that satisfaction is a key determinant of loyalty. Other factors that explain students’ loyalty are entrance marks and academic preferences (university and academic degree). Also, a further examination of the students’ profiles reveals that three different groups can be identified: loyal and satisfied students who did not enrolled in their most preferred academic option (first choice), unsatisfied students, and a group of loyal and satisfied students. Implications for policy and practice are discussed.